Manajemen dan Kepemimpinan PTK di SMK Negeri 3 Lubuk Sanai Kabupaten Mukomuko - Fadel Muhammad Fakhri; Hasan Maksum; Wawan Purwanto (Journal on Education, 2024)
This journal discusses the management and leadership of Classroom Action Research (PTK) at SMK Negeri 3 Lubuk Sanai, Mukomuko Regency. The aim is to improve the quality of learning and create a supportive environment for student growth and development. PTK management at this school is carried out using modern management principles that are adaptive and responsive to change. The steps include setting goals and objectives, comprehensive planning, continuous implementation, as well as continuous evaluation and improvement. PTK leadership in this school is not only about providing instructions, but also about empowering all school members to actively participate in the learning process. This leadership is realized through inspiration and motivation, collaboration and communication, empowerment and professional development, as well as fostering an inclusive learning culture. By implementing effective PTK management and leadership, SMK Negeri 3 Lubuk Sanai is determined to improve the quality of learning and create a supportive environment for student growth and development, so that every student will be ready to face future challenges with confidence and adequate knowledge.